Controllability analysis of Flyback converter with constant power load based on switched linear systems. (November 2022) - Hu, Wei; Ding, Zekang; Chen, Xinbing; Long, Xiaoli
Abstract: A converter cascaded system is usually used for power conversion. However, due to the increase of the number of converters in the cascaded system, the amount of power switches and circuit elements also increases accordingly, which makes it difficult to analyze the dynamic characteristics and design control strategy. To understand the control theoretical characteristics of converter cascaded system and provide a theoretical basis for circuit parameters analysis and manipulation strategy design, taking the Flyback converter cascaded system as an example, this paper establishes an accurate switching linear systems model, discusses the control theoretical characteristics of the system in detail by using the controllability theorems. The simulations and experimental results prove the correctness of the analysis.